Charter 77 still alive. The concept of non-political politics in the work of Ladislav Hejdánek - Hejduk, Tomáš (My University, 2017)
The article analyses Ladislav Hejdánek´s (1927) concept of non-political politic (asserted and validated in Charter 77, thus assisting the Charter’s incredible ability to be functional) and its possible meaning todays – in debates about the role of intellectuals, philosophers and regular citizens in politics.The fundamental characteristic of the concept is an expansion of the field regarded as political; more precisely, his concept of the nature of man as a political being resistant a) to the way power expands into the ideologically intellectual and private plane of life, and b) to the emancipation of power politics from civic life (interest politics) and intellectual life. This twofold resistance distinguishes nonpolitical politics from power (operational) politics and from interest politics (the ideological and intellectual clashes of civic society). The position of non-political politics versus power politics and the position of the intellectual (philosopher) versus the politician is weakened by the stronger, indeed, the only irreconcilable antithesis of the true politician and the pseudo-politician. Where the activities of the pseudo-politician are concerned, the ultimate horizon of his reasoning and behaviour is his party, or even he himself. The non-political politician, on the contrary, cares for the space for the method of politics formed by the mind; he cultivates the individual and the whole of society in their education in the broadest possible (philosophical) sense.
Živá Charta 77. Koncept nepolitické politiky v díle Ladislava Hejdánka
Keywords: nonpolitical politics; Charter 77; Hejdánek; nepolitická politika; Hejdánek; Charta 77